Low-Dose Cadmium Exposure Reduces Human Prostate Cell Transformation in Culture and Up-Regulates Metallothionein and MT-1G mRNA - Jaya P. Gaddipati; N.V. Rajeshkumar; Jason C. Grove; Susan V. M. Maharaj; Jose A. Centeno; Radha K. Maheshwari; Wayne B. Jonas (Dose-Response, 2003)
Chronic low-level exposure to environmental toxins, including cadmium (Cd), is a growing problem in the industrialized world. One promising strategy for protection from these toxins is the use of low-dose exposure of environmental chemicals to induce cell tolerance and recovery, a phenomenon known as “protective hormesis”. Hormetic [low-dose stimulatory] effects occur in a variety of systems and with a number of chemicals. Cd is a potent carcinogen in rodents and has also been linked to human lung and prostate cancers. In the present study, we have evaluated the protective effects of low and ultra-low dose, long-term Cd exposure in the normal human prostate cells, RWPE-1. Cells were exposed to low and ultra-low doses (0, 0 (S −36 ), 10 −6 , 10 −7 , 10 −18 , 10 −21 , 10 −32 , or 10 −36 M ) of Cd for 20 weeks followed by treatment with 10 −5 M Cd for another 8 weeks. Continuous exposure of RWPE-1 cells to 10 −5 M Cd results in malignant transformation. However, cells pretreated with low and ultra-low doses of Cd had delayed transformation compared with controls. In addition, the number of transformed cell mounds was lower in pretreated cells indicating that low and ultra-low dose exposure had protective effects against high-dose Cd induced carcinogenesis. The expression of metallothionein (MT), the primary Cd detoxification protein, was induced by low-dose exposure to Cd and maintained during the 20 weeks. In addition, MT-1G mRNA was up-regulated 2- to 3-fold by low-dose and ultralow-dose Cd exposures and may be the mechanism of protective hormesis in this model. MT-1G mRNA might also serve as a biological indicator of very low-dose environmental Cd exposure.